(S)‐4‐(4‐aminobenzyl)‐2‐oxazolidinone based 2‐azetidinones for antimicrobial application and luminescent sensing of divalent metal cations. (27th March 2020) - Baruah, Shyamal; Aier, Merangmenla; Puzari, Amrit
Abstract: The impact of linezolid as an antibiotic against gram‐positive bacteria has inspired synthetic chemists to use oxazolidinones as substrate molecule in the synthesis of newer scaffolds with important pharmacological implication. The oxazolidin‐2‐ones are key intermediates in the synthesis of many interesting biologically active compounds. Design and synthesis of a new series of (S)‐4‐(4‐aminobenzyl)‐2‐oxazolidinone based multifunctional azetidinones were accomplished. Synthesis of the scaffolds was performed through a multi‐step reaction process involving protection of amine functional group, conversion of protected (S)‐4‐(4‐aminobenzyl)‐2‐oxazolidinone to its acetic acid derivative and then to acid chloride, and finally coupled with different substituted aromatic imines under mild reaction conditions in presence of an appropriate base. Structural characterization was carried out using conventional spectroscopic techniques. The compounds were screened for their antimicrobial activity against gram‐positive and gram‐negative bacteria and were found to possess better and promising antimicrobial property than some of the reported antimicrobial drugs like disulfonamide and tetracycline. Additionally, the scaffolds also exhibit prominent sensing property for divalent metal cations like Cu 2+, Zn 2+, and Ni 2+, through fluorescence quenching effect. Abstract :